Physical Activity: A Multi-disciplinary Introduction - Gareth Stratton (Routledge, 2018)
Physical activity and its relationship to health is one of the great issues of our age. The causes of, and solutions to, physical inactivity are complex and multi-dimensional, and therefore the subject needs to be studied and understood from a variety of perspectives. This is the first textbook to provide a truly multi-disciplinary introduction to physical activity studies.Offering a complete foundation to the subject, it covers the basics of every core discipline from biochemistry, public health and biomechanics to physiology, sport psychology and sociology. It introduces a full range of topics across the physical activity curriculum, including behaviour change, motor skill development, nutrition, exercise prescription, public health policy, and physical education, providing a well-balanced and international perspective on each important issue. There is also a strong emphasis throughout the book on the practical, applied dimensions of physical activity, including innovative approaches to promotion and intervention tailored to every age range and environment.